Patient-centred Communication Discourse of In-home Medical Consultations for Older Adults - Kondo, Kayo (Multilingual Matters, 2022)
This book presents a comprehensive analysis of the use of patient-/person-centred communication in providing health care for ageing populations through an ethnographic approach to physician in-home medical consultations in Tokyo, Japan, alongside interviews with physicians
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022)
Keywords: Communication studies; Doctor/patient relationship; Social, group or collective psychology; MEDICAL / Physician & Patient; Communication in medicine -- Japan; Patient-centered health care -- Japan; Physician and patient -- Japan